Intravascular Glomus Tumor of the Wrist Causing Chronic Wrist Pain - Najd Mazhar, Farid; Shoushtarizadeh, Tina; Mirzaei, Alireza (Journal of Hand and Microsurgery, 2018)
Glomus tumors are glomus body neoplasms that most commonly occur in the subungual areas of the hand, typically characterized by small nodules associated with localized tenderness, cold sensitivity, and excruciating paroxysmal pain. Extradigital glomus tumors can present a diagnostic challenge because they are rare and usually accompanied by nonspecific symptoms. Intravenous origin of the glomus tumor, especially in the wrist, is much rarer. The authors here report an intravenous glomus tumor of the wrist presented with atypical features such as insensitivity to cold and a history of long-term pain, which led to the misdiagnosis of the lesion as extensor tendonitis. Following the excision of the tumor mass, the patient's pain completely disappeared and no further pain was reported afterward. As a result, the authors suggest a more careful workup for the correct diagnosis of glomus tumors with such atypical manifestations. They also suggest considering intravenous glomus tumor in the differential diagnosis of a chronic wrist pain.
Keywords: extradigital; intravenous; glomus tumor; wrist; chronic pain